SYNTHESIS OF METAL OXIDE NANOPARTICLES ON THE SURFACE OF POLYMERS BY THE SOL-GEL METHOD AND THEIR PROPERTIES (Scientific journal of the Fergana State University, 2025)
Due to their wide range of applications, polymer-based functional materials occupy a special place among other technological materials. Metal oxide-based polymer nanocomposites are of great scientific interest to scientists due to their unique electrical, optical, thermal, mechanical, catalytic and biomedical properties. In this work, the synthesis of ZnO nanoparticles by sol-gel method on the composite surface of locally derived polymeric material and their photocatalytic decomposition reactions in organic dyes were studied. Scanning electron microscopy (SEM), energy dispersive X-ray and IR spectroscopic analysis methods were used for physicochemical analysis of the functional material containing ZnO nanoparticles. The reaction of photocatalytic decomposition of functional polymer containing ZnO in aqueous solution of organic dye – methylene blue (MB) under the action of sunlight was studied.